Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan D’besto Cabang Darmaga Caringin Bogor, Jawa Barat - Estu Mahanani; Ilham Kudratul Alam (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2022)
This study aims to determine the effect of product quality, service quality and price either partially or jointly on customer loyalty D'Besto Darmaga Caringin Bogor Branch, West Java. The research method used is quantitative method, the sampling technique uses purposive sampling technique and the number of research samples is 87 respondents. The data analysis technique used multiple linear regression analysis and the hypothesis test was t-test, F-test and coefficient of determination which were processed with SPSS Version software. 21. The t-count value for product quality is 3.206 with sig 0.002, the t-count value for service quality is 3.971 with sig 0.00 and the t-count value for price is 2.522 with sig 0.014. And the F-count value is 16.006. All t-count values are greater than t-table and F-count values are greater than F-table, it can be concluded that product quality, service quality and price either partially or jointly have a positive and significant effect on customer loyalty D'Besto Darmaga Caringin Bogor Branch, West Java.